Diagnostic Challenges of Anaplastic Large Cell Lymphoma in a Resource-Limited Setting: A Case Report and Literature Review - Oluomachi Charity Nnachi; Innocent Paul Ezenwenyi; Augustine Ejike Okoye; Chinedu Obasi Akpa; Chukwuma Joseph Uzoigwe; Gabriel Chima Ugwu (Case Reports in Hematology)
Anaplastic large cell lymphoma (ALCL) is a rare variety of non-Hodgkin’s lymphoma with diverse morphologic variants. Due to the similarity of the different variants with other lymphoma entities, misdiagnosis may be inevitable when immunohistochemical and cytogenetic techniques are not available and histology alone is employed. We report a case of a 43-year-old woman with a seven-month history of neck swelling which was complicated by ulceration of the mass and pathological fracture of the right clavicle after two months delay in arriving at a correct diagnosis. Several attempts to arrive at definitive diagnosis using histology alone gave divergent reports which all misdiagnosed the case until it was sent to a facility outside the country. Our report highlights the limitations and challenges of histology in making a definitive diagnosis of ALCL and the overt importance of immunohistochemical and cytogenetic techniques which are largely unavailable in resource-constrained environment typical of tertiary centers in Nigeria and most sub-Saharan Africa countries.